Impact of Value Addition Trainings on Farm Women of Nayagarh District of Odisha - Jyotirmayee Udgata; Shelly Dash (Journal of Extension Education, 2016)
Value addition in agriculture predominantly offers a means to increase, rejuvenate and stabilize farm income. Value addition specifically to fruits and vegetables not only enhance the shelf life of the produce but also make it available in the off- season and reduces seasonal peak production loss. As the farm women are mostly involved in post harvest operation they need to be trained in this sector. Krishi Vigyan Kendra Nayagarh in its training programme always tried to aware and educate the farm women in this value addition sector.The study reported here explored, to what extent the training programmes of value addition specifically in fruits and vegetable had been changing the farm women’s perceived knowledge ,acquisition of skills and level of adoption of value addition practices. The results exemplified the impact of value addition trainings in instilling positive orientation in terms of the magnitude of perceived knowledge, acquisition of skills and adoption levels. Moreover, the findings of the study revealed significant positive correlation between the demographic characteristics with the perceived knowledge, skill acquisition and adoption level of value addition practices of the rural women of the sampled area.